Improving Student Activity and Learning Outcomes on Zakat Material through the Use of Chromebook Media at SD Negeri Ujong Nga - Ita Vitrianti; Cut Dewi (Journal of Action Research in Islamic Education, 2025)
Abstract set a maximum of 250 words, including keywords and article This Classroom Action Research was conducted on sixth-grade students of Ujong Nga State Elementary School, motivated by initial observations showing low student activity in seeking information during discussions, even tending to disturb other friends. This condition has an impact on low learning outcomes, where out of 27 students, only 10 students (37%) achieved scores above the Minimum Completion Minimum (KKM), while 17 students (63%) were still below the Minimum Completion Minimum (KKM). To overcome this problem, the researcher implemented Chromebook learning media in Religious Education and Character Education learning, especially on zakat material. The purpose of this study was to determine the effectiveness of using Chromebooks in improving student activity and learning outcomes. The study was conducted in three cycles through the stages of planning, implementation, observation, and reflection, with 16 sixth-grade Muslim students as research subjects. Data were collected through observation of activity, learning outcome tests, and documentation. The results of the study showed a significant increase, where learning activity increased from 72% in cycle I to 76.11% in cycle II, and reached 85.14% in cycle III. Learning outcomes also increased from 78.15% in cycle I to 85.56% in cycle II, and then to 86.70% in cycle III. Thus, the use of Chromebooks has proven effective in improving the activeness and learning outcomes of sixth-grade students at Ujong Nga Public Elementary School.